Comparison of atomization characteristics of model exhaust gas dissolved diesel and gasoline. (15th October 2016) - Ju, Dehao; Jia, Xiaoxu; Huang, Zhong; Qiao, Xinqi; Xiao, Jin; Huang, Zhen
Highlights: Model exhaust gas (80% N2 and 20% CO2 ) was to mimic exhaust gas recirculation. The difference between the fuel-only and MEG dissolved fuel atomization was limited. The droplets of MEG dissolved fuel were less uniform than the fuel-only sprays. The dissolved MEG has negative effect on the droplet sizes of gasoline. The dissolved MEG has positive effect on the droplet sizes of diesel. Abstract: This work is to compare the spray characteristics of the model exhaust gas (MEG) dissolved diesel and MEG dissolved gasoline actuated through a plain-orifice atomizer. Gas mixture (80% nitrogen and 20% carbon dioxide in mol) was blown into diesel or gasoline to mimic exhaust gas recirculation within the fuel, after which the fuel was actuated out through a 0.6 mm (in diameter) orifice with an injection pressure of 10 MPa, where the ambient condition was atmospheric. Transient images of the sprays were recorded by high speed camera. From the spray images, macroscopic characteristics such as the transient spray angle variations, and transient contour plots at various light intensity levels were analyzed using the multi-threshold image process. The results were also compared with the atomization behavior of diesel and gasoline without dissolved gas. The spray angles of the MEG dissolved fuel sprays were larger during the beginning, due to the explosive effect of the compressed CO2 with a sudden pressure drop during the actuation. Generally, the droplets of the MEG dissolved fuel sprays were less uniform than those of the fuel-only sprays, and the dissolved CO2 has negative effect on the droplet sizes of gasoline but positive effect on that of diesel. The difference between the fuel-only and MEG dissolved fuel atomization was limited at low dissolution pressure.